Reducing dynamic power consumption in synchronous sequential digital designs using retiming and supply voltage scaling. - Chabini, N.
The problem of minimizing dynamic power consumption by scaling down the supply voltage of computational elements off critical paths is widely addressed in the literature for the case of combinational designs. The problem is NP-hard in general. To address the problem in the case of synchronous sequential digital designs, one needs to move some registers while applying voltage scaling. Moving these registers shifts some computational elements from critical paths, and can be done by basic retiming. Integrating basic retiming and supply voltage scaling to address this NP-hard problem cannot in general be done in polynomial run time. In this paper, we propose to first apply a guided retiming and then to apply supply voltage scaling on the retimed design. We devise new polynomial time algorithms to realize this guided retiming, and the supply voltage scaling on the retimed design. Also, we show that the problem in the case of combinational designs is not NP-hard for some combinational circuits with certain structure, and give a polynomial time algorithm to optimally solve it. Methods to determine lower bounds on the optimal reduction of dynamic power consumption are also provided. Experimental results on known benchmarks have shown that the proposed approach can reduce dynamic power consumption by factors as high as 61% for single-phase designs with minimal clock period. Also, they have shown that it can solve optimally the problem, and produce converter-free designs with reduced dynamic power consumption. For large size circuits from ISCAS'89 benchmark suite, the proposed algorithms run in 15 s-1 h.
Keywords: NP-hard problem; Combinational circuits; Computational elements; Dynamic power consumption; Minimal clock period; Polynomial run time; Polynomial time algorithms; Single phase design; Supply voltage scaling; Synchronous sequential digital design